A robust salt-tolerant superoleophobic aerogel inspired by seaweed for efficient oil-water separation in marine environments - Li, Yuqi; Zhang, Hui; Fan, Mizi; Zhuang, Jiandong; Chen, Lihui (Physical chemistry chemical physics : PCCP, 2016)
Oil-water separation has recently become an important subject due to the increasing incidence of oil spills. Materials with underwater superoleophobic properties have aroused considerable interest due to their cost-effectiveness, environmental friendliness and anti-fouling properties. This paper presents a robust salt-tolerant superoleophobic aerogel inspired by seaweed used without any further chemical modification for oil-seawater separation. The green aerogel is prepared by freeze-drying of sodium alginate (SA)-nanofibrillated cellulose (NFC) using Ca 2+ ions as the crosslinking agent. The three-dimensional (3D) interconnected network structure of the developed aerogel ensures its high mechanical strength and good flexibility. The natural hydrophilicity of the polysaccharides contained in the aerogel ensures its excellent underwater superoleophobicity, antifouling and salt-tolerance properties. More impressively, the as-prepared aerogel can even keep its underwater superoleophobicity and high hydrophilicity after being immersed in seawater for 30 days, indicating its good stability in marine environments. Furthermore, the aerogel could separate oil-seawater mixtures with a high separation efficiency (of up to 99.65%) and good reusability (at least 40 cycles). The facile and green fabrication process combined with the excellent separation performance and good reusability makes it possible to develop engineering materials for oil-water separation in marine environments. A robust salt-tolerant superoleophobic aerogel was fabricated by a simple combined freeze-drying and ionic cross-linking method for oil-seawater separation.